2012
DOI: 10.1111/j.1600-0765.2012.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CCL28, interleukin‐8, interleukin‐1β and tumor necrosis factor‐alpha in subjects with gingivitis, chronic periodontitis and generalized aggressive periodontitis

Abstract: CCL28, IL-8, IL-1β and TNF-α may play key roles in the host response to inflammation in periodontal diseases. As the severity of periodontal diseases increases, destruction of periodontal tissues also increases. Inflammation is one among many factors that trigger periodontal tissue destruction. Identification of the mediators that influence the development and progression of inflammation in periodontal diseases may be very important in understanding the prognoses of periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 55 publications
5
119
0
5
Order By: Relevance
“…20 The chemokine (C-C motif) ligand 28 (CCL28) is a novel marker for the diagnosis of gingivitis and periodontitis. 21 Previous studies have shown CCL28 is associated with increased epithelial inflammation. [22][23][24] The production of IL-1b increases following contact with a microbial stimulus, which in turn significantly increases the expression of CCL28.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…20 The chemokine (C-C motif) ligand 28 (CCL28) is a novel marker for the diagnosis of gingivitis and periodontitis. 21 Previous studies have shown CCL28 is associated with increased epithelial inflammation. [22][23][24] The production of IL-1b increases following contact with a microbial stimulus, which in turn significantly increases the expression of CCL28.…”
Section: Introductionmentioning
confidence: 96%
“…[22][23][24] The production of IL-1b increases following contact with a microbial stimulus, which in turn significantly increases the expression of CCL28. 21 To our knowledge, there are no studies evaluating the effectiveness of curcumin as a topical chemotherapeutic agent for periodontal disease. Curcumin has a combined anti-inflammatory, antioxidant and antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%
“…Os níveis de ICAM-1, IL-1β, 1L-17, M-CSF e TNF-α estavam mais elevados nos pacientes com PA do que nos pacientes saudáveis, com diferenças estatisticamente significantes, resultados semelhantes a outros estudos (Duarte et al, 2010;Shaddox et al, 2007;Ertugrul et al, 2013;Cifcibasi et al, 2015), Apenas a IL-10 foi estatisticamente maior no grupo saudável, como esperado, já que é uma citocina anti-inflamatória.…”
Section: Resultsunclassified
“…Procurando comparar os níveis da quimiocina epitelial associada à mucosa (CCL28), da IL-8, da IL-1β e do TNF-α, Ertugrul et al (2013) analisaram o fluido gengival de pacientes portadores de PAG, pacientes com PC, pacientes com gengivite e sujeitos periodontalmente saudáveis, e observaram que esse biomarcador estava em concentrações mais elevadas nos indivíduos com PAG, quando comparados com PC, gengivite e saudáveis.…”
Section: Il-8unclassified
“…Concentrations of IL-8 and IL-1β in gingival crevicular fluid are known to correlate with periodontal disease severity (Ertugrul et al, 2012). Multiple oral bacteria, in both planktonic and biofilm form, are known to induce IL-1β and IL-8, and other proinflammatory cytokines, from human oral epithelial cells (Peyyala et al, 2012).…”
Section: Discussionmentioning
confidence: 99%